Self-confidence, commitment and goal-setting in Czech athletes at different performance levels - Vicar, M. (Acta Gymnica, 2018)
Background: Numerous studies rank self-confidence, commitment and goal-setting among the foundation mental skills in athletes, conditioning the development of elite performance and also contributing to achieving first rate results during competition. Their quality is, therefore, essential for top performance.